If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(3x + -4) = 12 Reorder the terms: 6 + -2(-4 + 3x) = 12 6 + (-4 * -2 + 3x * -2) = 12 6 + (8 + -6x) = 12 Combine like terms: 6 + 8 = 14 14 + -6x = 12 Solving 14 + -6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -6x = 12 + -14 Combine like terms: 14 + -14 = 0 0 + -6x = 12 + -14 -6x = 12 + -14 Combine like terms: 12 + -14 = -2 -6x = -2 Divide each side by '-6'. x = 0.3333333333 Simplifying x = 0.3333333333
| (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | 3t+4=16 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | A=2x+2y | | -6x^2+5x+6=1.41666 | | -3+6x=5x-13 | | 8y-9=2-88yip | | 6/5x-8=3/4x | | 27+2x+5+3x-4=180 | | (3x^2+3x-8)+(3x^2+6x+17)-(6x^2-17)= | | ax^2+5x+6=1.41666 | | 6/5x-8=3/4x | | 6/5x-8=3/4x | | -3+6x=5x-13 | | -3+6x=5x-13 | | 9(x-8)+28=9x-44 | | 6/7*7/8 | | 27+2x+5+3x-4=180 | | -9(9+u)-2u=-10 | | 3t+4+t=6 | | (3t^4)(-2t)(5t^6)=x | | -9(9+u)-2u=-10 | | -3+6x=5x-13 | | 6/7*7/8 | | 6/7*7/8 | | 5x+10y=-20findx | | x=56-3x | | 3t+4+t=6 | | 25-2x=-(-6+7) | | 6w-5= | | 6w-5= |